Cenas da enunciação e ethos em narrativas sobre a expedição Roncador-Xingu : uma análise discursiva - Sancho, Karla Amorim (2014)
This research is embedded in the field of Discursive Studies, having as general purpose to perform a Discursive Analysis from part of literary and press coverage related to The Roncador-Xingu Expedition. This research carried out a Discursive Analysis, which is French-scholar-guided. It evaluated writings that constitute the book The Western March: the Epic Roncador-Xingu Expedition as well as the movie Xingu. Both book and movie gave a narrative of the main events of the Expedition that had been conducted within the midst of Brazil since 1944 culminating with the creation of the Xingu National Park in 1961. Having the Discursive Analysis as a methodological approach, this study investigated statements (re) produced in The Roncador-Xingu Expedition in a materialist conception, whose discursive effects are on the basis of the constitution of that event. Those effects do not sort themselves out in a converging point, though they engage themselves in social-historical contradictions. In this perspective, our study aimed to investigate the reasons that the narratives regarded to The Expedition shaped mostly euphoric images about the role of the Villas Boas brothers leading the Roncador-Xingu Expedition. For that, it was used the following analysis categories: enunciation scenes; generic scene; scenography and Ethos. What interested us most was specifically both to describe and to interpret the linguist-discursive resources mobilized in the enunciation scenes, which composed narratives, at the same time silencing the possibility to produce dysphoric senses regarding to the Villas Boas brothers. In other terms, we will pursue to describe and to interpret the discursive strategies used by the enunciators of such narratives, designated to erase any contradiction of meaning that is non-euphoric ones and yet to cover up the existence of a conflicting relationship between whites and indigenous.